Implementation of PjBL to Increase Activeness in Pancasila Education Learning in Grade III Elementary School - Nailil Muna; Nova Yulita; Putri Windarti; Salma Febriana; Eva Nur Hidayah (EDUCATION JOURNAL OF INDONESIA, 2025)
This study aims to describe the implementation of the Project-Based Learning model as an effort to increase student engagement in Pancasila Education learning in third-grade elementary school. The issue raised focuses on the low participation of students, who were previously only passive listeners during the learning process. This study used descriptive qualitative methods to gain an in-depth understanding of the process and results of Project-Based Learning implementation. The results indicate that Project-Based Learning has increased student engagement in cognitive, social, and emotional aspects through collaborative investigations, discussions, and project completion. Students appeared more confident in asking questions, expressing opinions, and working collaboratively in groups. Furthermore, project presentations helped boost student self-confidence. However, this study also found that the classroom atmosphere became less conducive due to high student enthusiasm, necessitating more effective classroom management strategies. Overall, Project-Based Learning has been shown to positively contribute to increasing student engagement in Pancasila Education learning..   Keyword : Project Learning, Student Engagement, Pancasila Education, Elementary School, Learning Engagement.